1987
DOI: 10.1007/bf00733789
|View full text |Cite
|
Sign up to set email alerts
|

The modulation of excitatory amino acid responses by serotonin in the cat neocortexin vitro

Abstract: 1. The electrophysiological actions of excitatory amino acids and serotonin were investigated in slices from cat neocortex in vitro. Intracellular recordings were obtained from neurons (mainly in layer V) and the drugs applied extracellularly to the same neurons by microiontophoresis. 2. Serotonin, and to some extent noradrenaline, facilitated the excitatory actions of N-methyl-D-aspartate (NMDA), glutamate, and quisqualate but caused no changes in the passive neuronal membrane properties when presented alone.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
29
0

Year Published

1991
1991
2007
2007

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 75 publications
(32 citation statements)
references
References 26 publications
3
29
0
Order By: Relevance
“…This suggestion is consistent with evidence showing that blocking phosphatidylinositol turnover or elevating Ca 2ϩ levels affects plasticity in the visual cortex (17). In addition, 5-HT has been shown to facilitate the excitatory actions of N-methyl-Daspartate and glutamate in cat and rat neocortical slices (18,19). The enhanced N-methyl-D-aspartate response evoked by 5-HT application was long lasting and irreversible (19).…”
Section: Discussionsupporting
confidence: 88%
“…This suggestion is consistent with evidence showing that blocking phosphatidylinositol turnover or elevating Ca 2ϩ levels affects plasticity in the visual cortex (17). In addition, 5-HT has been shown to facilitate the excitatory actions of N-methyl-Daspartate and glutamate in cat and rat neocortical slices (18,19). The enhanced N-methyl-D-aspartate response evoked by 5-HT application was long lasting and irreversible (19).…”
Section: Discussionsupporting
confidence: 88%
“…Serotonin also increased the proportion of glutamate containing neurons in embryonic cortical slices without affecting the proportion of other neuronal or glial cell types [72]. In vitro electrophysiologic studies demonstrated that exogenous application of 5-HT produces enhanced excitatory NMDA-evoked responses in rat [98] and cat [89] neocortical slices. Rodent studies in vivo showed that 5-HT was present during critical periods of postnatal rat [41,78,90] and mouse [59] cortical development and shows a more prevalent peak in male BALB/CbyJ mice [31].…”
Section: Discussionmentioning
confidence: 92%
“…Activation of G-protein complexes requires Mg2+ (Birnbaumer et al, 1990;Litosch, 1991); removal of extracellular Mg2 + which presumably lowers the concentration of Mg2+ in the cytosol (Heinonen & Akerman, 1986), is sufficient to depress the muscarinic AChR-evoked depolarization of neocortical neurones (El-Beheiry & Puil, 1990). Thus, it is plausible that the Mg2+-dependence of the facilitation induced by G-protein coupled receptors reflects the regulatory role of Mg2+ in signal transduction associated with these receptors, rather than loss of voltage-dependence at the NMDA receptor-gated ion channel (Chen & Huang, 1992; see also Nedergaard et al, 1987). Such a mechanism would account for the insensitivity of the calcimycin facilitation to the reduction in Mg2+.…”
Section: Discussionmentioning
confidence: 99%